Legal interpretation of modern security risks - Bardžić Žikica; Miladinović-Bogavac Živanka (Oditor, 2023)
With globalization, we have a pronounced paradigm of a risky society. That paradigm arises due to the uncontrolled production of socioeconomic, environmental and military risks. If we add to that the relativization of social differences and boundaries, then as a result we have an increase in insecurity and insecurity. The land and territories that have been "eaten" by globalization become an unreliable place to live. All of the above has the effect that transnational processes, the global market and democracies do not necessarily mean peace, but on the contrary very often insecurity, riots, conflicts and bloody wars. Although the value of current processes based on integrative theories and emphasizing common interests cannot be disputed, the paradigm of a harmonious world is too far from reality. It is undeniable that insecurity and insecurity have increased in the world with the process of globalization.